2018
DOI: 10.1590/0103-8478cr20170638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warm-up intensity on horse-rider dyad’s performance in jumping

Abstract: The aim of this study was to determine whether there is a correlation between the intensity of warm-up and scores of horse-rider dyads in jumping competitions, and which factors affect the warm-up regime. Three international competitions of 120, 130, and 135cm obstacle height, completed by 82 competitors, were studied. Warm-up intensity was measured by the time spent in the schooling area, number of practice jumping efforts, and coefficient of practice obstacle height. Out of the official final scores in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…While the cognitive abilities of horses have been explored in a range of studies (reviewed in 8 ), the potential effects of exercise on equine cognition have not been tested experimentally. In common with human athletes, domestic horses are routinely exposed to a physical warm-up prior to a training session or competition because of perceived physical and mental benefits 9 , however in one study, warm-up intensity was found to be negatively correlated with subsequent performance in a show jumping competition 10 .…”
Section: Introductionmentioning
confidence: 99%
“…While the cognitive abilities of horses have been explored in a range of studies (reviewed in 8 ), the potential effects of exercise on equine cognition have not been tested experimentally. In common with human athletes, domestic horses are routinely exposed to a physical warm-up prior to a training session or competition because of perceived physical and mental benefits 9 , however in one study, warm-up intensity was found to be negatively correlated with subsequent performance in a show jumping competition 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Six studies described warm-up strategies in show jumping horses and their effects on performance [ 49 , 51 , 52 , 53 , 54 , 55 ]. The mean warm-up durations in these studies are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…From 2 to 15 jumps were used during warm-up, and the performance in the show ring, expressed as the number of faults, was not associated with the warm-up routine. However, another study of 82 competitors found that, while warm-up duration did not affect the score in the ring, more jumps and higher obstacles during warm-up decreased performance [ 54 ]. Tranquille et al [ 53 ] found no difference in the warm-up duration, the time in each pace, and on each rein, mean, peak, and final warm-up HR in 10 elite horses over three consecutive days.…”
Section: Resultsmentioning
confidence: 99%
“…Although the use of warm-up in equestrianism is beyond dispute, there have been few studies into its effect on horse performance. According to Stachurska et al [14], the warm-up duration had no impact on the final result of the jumping competition while older showjumping horses obtained a shorter warm-up than younger horses. Murray et al [15] reported that warm-up duration increased with the level of dressage competition and can be positively associated with final score.…”
Section: Introductionmentioning
confidence: 99%